Size‐dependent predation and correlated life history traits alter eco‐evolutionary dynamics and selection for faster individual growth. Issue 1 (5th March 2018) - DeLong, John P.; Luhring, Thomas M.
Abstract: Age at maturation is a key life history trait influencing individual fitness, population age structure, and ecological interactions. We investigated the evolution of age at maturity through changes in the von Bertalanffy growth constant for organisms with a simple juvenile‐adult life history. We used Gillespie eco‐evolutionary models to uncover the role of predation in driving the evolution of the growth constant when eco‐evolutionary dynamics are present. We incorporated both size‐independent and size‐dependent predation into our models to generate differences in selection and dynamics in the system. Our results generally support the idea that faster ontogenetic growth is beneficial when populations are growing but that predation tends to have little effect on age at maturity unless there are trade‐offs with other life history traits. In particular, if faster ontogenetic growth comes at the cost of fecundity, our results suggest that predation selects for intermediate levels of growth and fecundity. Eco‐evolutionary dynamics influenced the nature of selection only when growth was linked to fecundity. We also found that predators that increasingly consume larger prey tend to have higher population sizes due to the greater energy intake from larger prey, but the growth rate‐fecundity trade‐off reversed this pattern. Overall, our results suggest an important role for interactions between size‐dependent foraging and life‐history trade‐offs in generating varying selection on age at maturity through underlying growth traits.